Host Immune Evasion by Lyme and Relapsing Fever Borreliae: Findings to Lead Future Studies for Borrelia miyamotoi - Stone, Brandee L.; Brissette, Catherine A. (Frontiers in Immunology, 2017)
The emerging pathogen, Borrelia miyamotoi, is a relapsing fever spirochete vectored by the same species of Ixodes ticks that carry the causative agents of Lyme disease in the US, Europe, and Asia. Symptoms caused by infection with B. miyamotoi are similar to a relapsing fever infection. However, B. miyamotoi has adapted to different vectors and reservoirs, which could result in unique physiology, including immune evasion mechanisms. Lyme Borrelia utilize a combination of Ixodes-produced inhibitors and native proteins (i.e. factor H-binding proteins/CRASPs, p43, BBK32, BGA66, BGA71, CD59-like protein) to inhibit complement, while some relapsing fever spirochetes use C4b-binding protein and likely Ornithodoros-produced inhibitors. To evade the humoral response, Borrelia utilize antigenic variation of either outer surface proteins (Osps) and the Vmp-like sequences (Vls) system (Lyme borreliae) or variable membrane proteins (Vmps, relapsing fever borreliae). B. miyamotoi possesses putative factor H-binding proteins and antigenic variation of Vmps has been demonstrated. This review summarizes and compares the common mechanisms utilized by Lyme and relapsing fever spirochetes, as well as the current state of understanding immune evasion by B. miyamotoi.